Flexible Bus Media Redundancy - Silva, Valter (2007)
This paper proposes a flexible approach to bus media redundancy in Controller Area Network (CAN) fieldbuses, both to improve the bandwidth by transmitting different traffic in different channels or to promote redundancy by transmitting the same message in more than one channel. Specifically the proposed solution is discussed in the context of Flexible Time-Triggered protocol over CAN (FTTCAN) and inherits the online scheduling flexibility of FTTCAN, enabling on-the-fly modifications of the traffic conveyed in the replicated buses. Flexible bus media redundancy is useful to fulfill application requirements in terms of additional bandwidth or to react to bus failures leading the system to a degraded operational mode, without compromising safety. The arguments for and against flexible bus media redundancy in the context of FTT-CAN are also discussed in detail.